Measuring Learners’ Scientific Literacy Skills using Contextual Environmental Issues - Monica, Elsa; Suprapto, Nadi; Budiyanto, Mohammad; Satriawan, Muhammad; Cheng, Tsung-Hui (FKIP Universitas Lampung, 2024)
Learners' science literacy skills in science learning activities become an important ability for learners to face the times. The ability of learners to respond to contextual topics can show the qualifications of their science literacy skills. The research conducted aims to describe the science literacy skills of students at the Islamic Junior High School level on environmental issues that occur around them. Through descriptive quantitative method, the researcher presents the results of students' science literacy ability in working on contextual questions based on environmental issues along with supporting and inhibiting factors in supporting learning activities. The study involved 25 students at one of the Islamic Junior High School in Jombang. Based on the analysis of the profile of students' science literacy skills at one of the Islamic Junior High School in Jombang, it was found that the general average score of science literacy skills of grade 7 students was 44.72 in the low category. There are several factors that cause the low science literacy skills of these students, including interest in learning, learning strategies, and learning facilities that still need to be optimised. Keywords: science literacy, environmental, contextual issue. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1648-1664